A PERSON WITH A DISABILITY AND ITS PROBLEMS IN MODERN SOCIETY (American Journal of Interdisciplinary Research and Development, 2024)
This article examines the social, economic, and psychological problems faced by people with disabilities, their rights, and their place in society. Additionally, the study explores attitudes towards individuals with disabilities, societal stigma, as well as rehabilitation and integration mechanisms accordingly.